Streetwear e mídias sociais: uma análise cultural da Steal The Look - Santos, Diovana Vieira dos (2025)
The research proposed here investigates the transformation of streetwear into a global trend and its role in the construction of identities and representation in consumer society and the digital environment. Starting from the understanding of streetwear as a cultural and social phenomenon, its trajectory from marginality to mainstream is analyzed, highlighting how the style was appropriated by the market and resignified by social media. The methodology adopted is based on media cultural analysis (Steffen, Henriques and Filho, 2020), which allows us to understand how streetwear is represented and consumed in the digital world. Steal The Look content on Instagram was analyzed and semi-structured interviews were conducted with consumers from different contexts. The intention is to understand how these individuals perceive and relate to streetwear. This dissertation is based on a theoretical basis composed of authors who analyze the relationship between fashion, consumption, identity and culture. Stuart Hall (1997, 2016) and Nestor García Canclini (1999) contribute to the understanding of identity and cultural consumption as spaces of meaning and belonging. Pierre Bourdieu (1984) and Grant McCracken (1986) explore consumption as a social marker, while Douglas and Isherwood (2006) analyze its role in structuring values and social relations. In the field of fashion, Diana Crane (2006) investigates its role in the construction of class and identity, while Barnard (2003) discusses fashion as a form of communication. Simmel (2008) presents the concept of trickle effect, essential to understanding the spread of streetwear from the underground to the mainstream. Palomino (2002) and Parry (2018) address the commercialization of this style, highlighting its appropriation by the market. The research also draws on Cultural Studies, with contributions from Escosteguy (2009) and Ronsini (2007), in addition to qualitative methodologies developed by Duarte (2005) and Steffen, Henriques and Filho (2020), who analyze the role of digital media in cultural mediation. The dissertation articulates these perspectives to understand the trajectory of streetwear and its impact on the construction of contemporary identities. The results show that streetwear goes beyond the sphere of clothing, becoming a space for identity expression and symbolic dispute. While social media expands its reach and democratizes access to fashion, it also imposes standards that can limit diversity and reinforce the logic of mass consumption. Thus, the research highlights the duality of streetwear in the digital world: between resistance and commercialization, between identity and standardization.